PENERAPAN SYARAT MATERIIL SURAT DAKWAAAN PIDANA PENGEROYOKAN PADA PUTUSAN NOMOR : 813/PID.B/2023/PN.SBY: The Application of the Material Requirements of the Indictment for the Crime of Assault in Decision Number: 813/PID.B/2023/PN.SBY - Rizki Firdaus Nuryana Basri; Maria Silvya E. Wangga (Reformasi Hukum Trisakti, 2024)
The Public Prosecutor is responsible for prosecuting, beginning with the reading of the indictment. However, in practice, some indictments do not meet the requirements set out in the Indonesian Criminal Procedure Code (KUHAP), as seen in Decision Number 813/PID.B/2023/PN.SBY. The research questions are how the indictment for the crime of assault was applied in decision number 813/PID.B/2023/PN.SBY and what are the legal consequences of an inaccurate indictment by the Public Prosecutor in this case, according to KUHAP. This research uses a normative juridical method with a descriptive-analytical approach, relying on secondary data and primary legal materials analyzed qualitatively. The conclusions drawn are that the indictment in Decision Number 813/PID.B/2023/PN.SBY is a cumulative-alternative combination but fails to meet the material requirements of KUHAP. The Public Prosecutor’s negligence in repeating the same article within the indictment reflects a lack of diligence, resulting in a vague indictment that contradicts the principles of criminal procedure law. Such an indictment opens the door for the defense counsel to file an exception, potentially leading to the judge rejecting the indictment and the case being dismissed by law